Research & Application of Locomotive Synchronous Control Remote Monitor Platform - GUO Jin-zhao; DENG Ya-bo; WU Hang (机车电传动)
Locomotive synchronous control remote monitor platform for a certain ten-thousand-ton reconnected locomotive was proposed. With running information real-time collect, modern communication and signal processing, remote monitoring and fault diagnosing for ten-thousand-ton reconnected locomotive were implemented. At the same time, rich data could support locomotive operation, maintenance, service and information management, which helped to realize flow process informatization.